Effect of external stress anisotropy on the ferromagnetic resonance properties in thin film. (22nd September 2022) - Zhou, Jieyu; Rong, Jianhong; Wang, Huan; Zhang, Shufei; Liu, Ling
Abstract: Effects of in-plane and out-of-plane external stress anisotropy of ferromagnetic thin film with in-plane and out-of-plane uniaxial anisotropy on the ferromagnetic resonance frequencies have been theoretically investigated by using ferromagnetic resonance method. It is shown that resonance frequency can be enhanced by increasing in-plane external stress anisotropy field and uniaxial anisotropy field, decreasing out-of-plane uniaxial anisotropy field. For out-of-plane external stress case, however, the resonance frequency and two critical fields have no significant change. Also, compared with the case of the in-plane external stress anisotropy, the FMR frequencies are smaller. Additionally, interesting features are obtained for the stress case and compared with the case of without stress. The obtained results provide further insights on the effect of external stress on the properties of ferromagnetic thin film.